Mind the gap: A critical reflection on hotel employee turnover - Mohsin, A.; Brochado, A.; Rodrigues, H. (International Journal of Contemporary Hospitality Management, 2023)
Purpose: This study aims to provide a critical reflection research that was carried out to understand more fully how employee turnover has been critical to hotel management’s strategies for constructing a better workplace. Human resources decisions need to be made carefully based on a clear grasp of their effects on hotels and their staff. Design/methodology/approach: A critical review was conducted with a sample of 160 academic papers that reported findings on staff turnover intentions in hotels. Findings: The results include a concept map that highlights the two main dimensions found by researchers: hotel staff turnover consequences (i.e. customer satisfaction and financial performance) and antecedents (i.e. individual, job-related, relationship, organisational and opportunities). Research limitations/implications: The findings underline that staff retention strategies need to focus on managing job-related, organisational and relationship variables as hotel managers have little influence on individual and job opportunity factors. Originality/value: This study examined 20 years of research summarised in an up-to-date conceptual map. The findings have cross-disciplinary implications.